Malaysian contract farmers’ attitude towards sustainable agriculture - Abu Samah, Bahaman; D’Silva, Jeffrey Lawrence; Mohamed Shaffril, Hayrol Azril; Man, Norsida; Azman, Azmariana (TextRoad Publication, 2012)
This study attempts to discover the attitude of contract farmers towards sustainable agriculture. A total of 326 contract farmers from four selected states in Malaysia were randomly selected as the respondents for this study. The findings reveal that the contract farmers surveyed have a favourable attitude towards contract farming. Inferential statistics unveiled that two demographic factors, namely zone and race, show significant differences in terms of attitude towards sustainable agriculture, while age was found to be negatively correlated with it. It is recommended that more courses and seminars should be conducted to further promote favourable attitudes towards sustainable development among contract farmers, and that access to financial support and knowledge of sustainable agriculture should be increased. In addition, to add our understanding on farmers’ attitudes towards sustainable agriculture, more research should be conducted in this area.